1988
DOI: 10.1007/bf03350094
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypothyroidism due to leukemic infiltration of the thyroid gland

Abstract: We describe a patient with acute B-lymphocyte lymphoblastic leukemia who developed laboratory changes (not detectable free thyroxine, TSH 66 microIU/ml) suggesting severe primary hypothyroidism. Histological examination at autopsy showed massive leukemic infiltration of the thyroid gland: the progressive reduction of thyroid hormone levels with concomitant increase in TSH levels observed over a three-month period from the onset of the hemopathy suggests a cause-effect relationship between leukemic infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…According to our knowledge, thyroid nodule as the first presentation of the ALL had not been reported before. It is worthy to note that most of the extramedullary thyroid involvements in the case reports manifested as hypothyroidism (5, 6). On the other hand, the most common lymphoproliferative disorder involving thyroid gland is lymphoma; however, it is an uncommon thyroid malignancy (7) and hence, thyroid leukemic infiltration has not any place in thyroid malignancies classification (8).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to our knowledge, thyroid nodule as the first presentation of the ALL had not been reported before. It is worthy to note that most of the extramedullary thyroid involvements in the case reports manifested as hypothyroidism (5, 6). On the other hand, the most common lymphoproliferative disorder involving thyroid gland is lymphoma; however, it is an uncommon thyroid malignancy (7) and hence, thyroid leukemic infiltration has not any place in thyroid malignancies classification (8).…”
Section: Discussionmentioning
confidence: 95%
“…Based on a case series study, most of the ALL induced thyroid functional disorders, occurred during off-therapy follow-up because of thyroid gland damage by chemotherapy; moreover, hyperthyrotropinemia was reported in some patients after ALL chemotherapy (5). Although one case of primary hypothyroidism reported due to leukemic infiltration of thyroid gland (6), herein, we reported a case of ALL that was detected with thyroid nodule as its first presentation.…”
Section: Introductionmentioning
confidence: 82%
“…Foresti et al [12] reported a patient with acute B cell lymphoblastic leukemia who developed primary hypothyroidism. The authors reported that direct infiltration of leukemic blasts to the thyroid induced hypothyroidism in their patient, who had elevated TSH concentrations and low FT4 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Lösemi hastalarında nadir olarak tiroid tutulumu görüleblir (9)(10)(11)(12). Metastatik yayılımlarda tiroid işlevleri genellikle değişiklik göstermez ancak daha sıklıkla hipotiroidi görülmek üzere bazı olgularda da hipertiroidi saptanmıştır.…”
Section: Discussionunclassified